Non Union of Fracture Neck of Femur for Intertrochanteric Osteotomy - Singh, GP (Journal of Universal College of Medical Sciences, 2013)
BACKGROUND: Femoral neck fracture is a difficult problem in adult patients and without proper treatment leads to high functional impairment and frequent complications. OBJECTIVE: The aim of this study was to see the functional outcome in patients with non union of fracture neck of femur treated with intertrochanteric osteotomy. MATERIAL AND METHODS: All 14 cases operated and non operated (neglected) fracture neck of femur were enrolled for the study 2003 to 2009 in National Medical College, Birganj and Janaki Medical College, Janakpur. Patients were treated conservatively and in some patients failure of fixation was used to evaluate the functional outcome. RESULTS: There were 14 patients with average age of 30 years with age range 14-50 years. 8 patients were male and six were female. 10 patients were previously treated conservatively and 4 patients presented with failure of fixation. Average duration of fracture was 7 months (2 months -3 years with pauwel angle of 32.8. CONCLUSION: Neglected neck of femur fracture should be treated by three cancellous screw fixation with molded and angled narrow DCP plate, valgus osteotomy and autogenous bone grafting round the fracture to achieve a high rate of patient satisfaction and satisfactory functional outcome. DOI: http://dx.doi.org/10.3126/jucms.v1i3.8762 Journal of Universal College of Medical Sciences Vol.1(3) 2013: 33-36